Hemodynamic responses to strength exercise with blood flow restriction during different phases of the menstrual cycle - Gabriel Rodrigues Neto; Jefferson Silva Novaes; Adenilson Targino de Araújo Júnior; Júlio César Gomes Silva; Rodrigo Poderoso Souza; Maria Socorro Cirilo-Sousa (Desafio Singular, 2017)
The present study aimed to determine the influence of low-load (LL) resistance exercise (RE) with blood flow restriction (BFR) on systolic blood pressure (SBP), diastolic blood pressure (DBP), mean blood pressure (MBP), heart rate (HR), double product (DP) and oxygen saturation (SpO2) during the phases of the menstrual cycle (MC). Thirty untrained women were randomly and proportionally divided into three groups: HI = high-intensity exercises (80% of one-repetition maximum (1RM)); LL = low-load exercises (20% of 1RM); and LL+BFR = LL exercises combined with BFR. The exercise sessions were performed during the 3rd-4th days (follicular phase), 16th day (ovulatory phase) and the 24th-26th days (luteal phase) of the MC. Before and immediately after the exercises, SBP, DBP, HR and SpO2 were evaluated. We observed an increase in SBP, HR and DP in the three phases of the MC for all groups (p < 0.05). Groups LL and/or LL+BFR exhibited a greater increase in SBP, DBP, MBP, HR and DP when compared with the HI group (p < 0.05), and in the three groups, SpO2 was not reduced (p > 0.05). There was a significant effect of the MC phases on HR and DP (p < 0.05). We conclude that the three groups exhibited increased SBP, HR and DP; however, SpO2 was not different. Furthermore, groups LL and LL+BFR exhibited greater increases in hemodynamics, and the MC phases seem to influence only HR and DP.